PORTMANTEAUS IN INDONESIA FAMOUS PEOPLE NAMES: IDENTITY AND POWER - Yudhy S Purwanto; Neneng Yuniarty (Universitas Widyatama, 2020)
Indonesia can be considered as the most productive country that creates and uses portmanteau. The blending habit is practised in the peoples everyday life, and it covers almost all aspects, from the government programs up until peoples names. Apart from simplification reason, there are some other senses that may come together with the portmanteau, among others: the memorability logic, the handy label concern, and the power it bears. This research was aimed at the usage of portmanteau by Indonesian famous people and the power gained through those names. It uses the blending and neologism theories for the portmanteau formation and Fairclough power representation and Wodak Critical Discourse Analysis theories. A qualitative research method was used in order to understand the problem deeply and thoroughly. The results are that the usage of portmanteau names give some advantages to the bearer including values, respects, and powers.